Intensive Care Management in Pediatric Burn Patients - Ayşe Ebru Sakallıoğlu Abalı (Galenos Yayinevi, 2011)
Burn injury is still a leading cause of morbidity and mortality in children. This article aimed to review the current principles of management from initial assessment to early management and intensive care for pediatric burn patients. (Journal of the Turkish Society Intensive Care 2011; 9 Suppl: 62-9)